Usage of a binary integrated spell check algorithm for an upgraded search engine optimization. (December 2022) - Gowri, S.; Sathish Kumar, P.J.; Geetha Rani, K.; Surendran, R.; Jabez, J.
Abstract: Search engines have become an integral part of our lives. To augment the power of such engines - even while offline - was our goal. To accomplish this, a distinct offline search engine was created to retrieve data from archives. An updated UI was achieved to make interacting with the software more appealing and convenient. A spell check technique to recommendations emanated from the assessed query is the most major addition to the interface. The general goal is to make offline search engines more accessible to use. To provide satisfactory results with the spell check mechanism, to use a binary converter so that the query correction and evaluation become even more accurate.